Comorbidities, Social Impact, and Quality of Life in Tourette Syndrome - Eapen, Valsamma; Cavanna, Andrea E.; Robertson, Mary M. (Frontiers in Psychiatry, 2016)
Tourette Syndrome (TS) is more than having motor and vocal tics, and this review will examine the varied co-morbidities as well as the social impact and Quality of Life (QoL) in individuals with TS. The relationship between any individual and his/her environment is complex and this is further exaggerated in the case of a person with TS. For example, tics may play a significant role in shaping the person’s experiences, perceptions and interactions with the environment. Further, associated clinical features, co-morbidities and co-existing psychopathologies may compound or alter this relationship. The common co-morbidities in this regard include Attention Deficit Hyperactivity Disorder (ADHD) and disruptive behaviours, Obsessive Compulsive Disorder (OCD) and Autism Spectrum Disorder (ASD), and co-existent problems include anxiety, depression and low self esteem, which can all lead to poorer psychosocial functioning and QoL. Thus, the symptoms of TS and the associated co-morbid conditions may interact to result in a vicious cycle or a downward spiralling of negative experiences and poor QoL. The stigma and social maladjustment in TS and the social exclusion, bullying and discrimination is considered to be caused in large part by misperceptions of the disorder by teachers, peers, and the wider community. Improved community and professional awareness about TS and related co-morbidities & other psychopathologies as well as the provision of multidisciplinary services to meet the complex needs of this clinical population are critical. Future research to inform the risk and resilience factors for successful long term outcomes is also warranted.